Perencanaan Strategis Sistem Informasi Menggunakan Metode Ward And Peppard Studi Kasus Cv XYZ - David Setya Wardhana; Andeka Rocky Tanaamah (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2019)
Global competition requires companies to move dynamically to the flow of change, one of the things that can be done is to use information systems. CV XYZ already has an information system but there are still some parts that have not implemented the information system. Retrieval of data in this study using interview and observation methods to determine the business environment and corporate information system environment. The method used in this study is Ward and Peppard with SWOT analysis, Value Chain analysis, Five Forces Porter, and Mc Farlan’s Strategic Grid. This research generates strategic recommendations, provides internal environmental analysis, external company information systems and proposed information systems namely HRD information systems, After Service information systems, Supplier information systems, Customer service information systems, Administrative information systems, and Promotional information systems, which are priorities in accordance with Mc Farlan's Strategic Grid mapping, and can be applied by the company within the next 3 (three) years.